Gender-preferential intergenerational patterns in primary educational attainment: An econometric approach to a case in rural Mindanao, the Philippines. (January 2016) - Okabe, Masayoshi
Abstract: This study investigates the factors determining children's educational attainment, focusing on gender-differential intergenerational patterns, by employing a case study from rural Mindanao. The result mainly shows, unlike general trends in developing countries, educational attainment is more favorable for girls; maternal education level is equally associated with daughters' and sons' education levels, and paternal education level is preferentially favorable to their sons. To reduce the disparity, suggestions include providing boy-specific interventions to enhance the magnitude of the father–son educational virtuous circle and comparing the magnitude of gender-equal maternal and boy-preferential paternal education influences to specify which effect is larger.